Study of tensile crack growth in rock-like materials under punch shear test. (October 2022) - Fu, Jinwei; Sarfarazi, Vahab; Haeri, Hadi; Shahbazian, Armin; Fatehi Marji, Mohammad; Yu, Yibing
Highlights: A punch test apparatus is developed to measure the direct tensile strength of rock-like materials based on the crack propagation process. The proper testing specimens of gypsum and concrete are specially designed for the punch tests. The direct tensile strengths of gypsum and concrete specimens are compared with the indirect (Brazilian) tensile strengths. The punch test is simulated with two dimensional explicit finite difference (FLAC2D) and particle flow code (PFC2D). The experimental and numerical results are compared with one another. Abstract: In this paper, the specification of tensile crack growth under punch shear test was studied. Also, direct and indirect tensile strength of gypsum and concrete (rock-like materials) were determined and compared in this research. The direct tensile strength was measured by a new apparatus using the cubic specimens with 20 cm * 20 cm * 5 cm in dimensions containing four edge notches. The indirect Brazilian tensile strength was measured with the Brazilian disc samples. The notch lengths were similar in one sample. Three different lengths were chosen for notches, i.e., 10 cm, 12 cm, 14 cm and 16 cm. Ligament lengths (horizontal distance between two notches ) was 2 cm. These samples were tested under a punch shear test. The numerical simulation of these tests was also performed with the Particle Flow Code (PFC) and the stresses within the specimen and the critical stress intensity factors were estimated with the explicit finite difference code (FLAC2D). Ligament lengths were 2 cm, 3 cm and 4 cm. In this work, the results of indirect tensile strength were higher than those measured directly in the laboratory. When the joint length was 10 cm, the tensile force was concentrated around the notch tips while it was concentrated at the ligament by increasing the notch length. In the fixed value of ligament length, the tensile force concentration was distributed uniformly in the ligament by enhancing the joint length. In the fixed value of joint length, the tensile force concentration was distributed uniformly in the ligament by increasing the ligament length. It was found that, as the length of the joints increase the value of tensile was decreased. On the other hand, the tensile strength was increased by decreasing the ligament length.